Mississippi in the Civil War : the home front - Smith, Timothy B., 1974- (Heritage of Mississippi series, 2010)
In Mississippi in the Civil War: The Home Front, Timothy B. Smith examines Mississippi's Civil War defeat by both outside and inside forces. The invading Union army dismantled the state's political system, infrastructure, economy, and fighting capability. The state saw extensive military operations, destruction, and bloodshed within her borders. One of the most frightful and extended sieges of the war ended in a crucial Confederate defeat at Vicksburg, the capstone to a tremendous Union campaign.